PREVALENCE OF HPV HIGH-RISK GENOTYPES IN THREE COHORTS OF WOMEN IN OUAGADOUGOU (BURKINA FASO) - Theodora M. Zohoncon; Jacques Simpore (Mediterranean Journal of Hematology and Infectious Diseases)
The development of cervical cancer is ​​associated with high-risk Human papilloma viruses (HPV-HR). In sub-Saharan Africa cervical cancer is the most common cancer among women and the leading cause of death attributed to malignant tumors. This study aims to identify HPV genotypes within the 30'S and 50'S HPV families found in two previous studies from our laboratory, and to determine the prevalence of twelve HPV-HR genotypes in a population of women in Ouagadougou.